(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article presents the results of research on improving the technology of effective collection of flammable liquids spilled at industrial enterprises, oil depots and vehicles before they ignite. At the same time, existing methods are analyzed and their advantages and disadvantages are compared. The article proposes a new technological solution - an approach based on a mobile aspiration and filtration system, which not only improves safety, but also meets environmental requirements.